Indian feminisms : individual and collective journeys - Kathuria, Poonam; Bhaiyā, Ābhā
One of the most dynamic feminist movements in the world, Indian feminisms are seldom given the recognition they deserve, not only for the essential work they do but for the successes they've had. This collection of essays, written by well-known activists and founders of prominent Indian feminist institutions, will change that. In addressing how women's oppression and discrimination lie at the intersection of complex inequalities of caste, religion, class, race, and ethnicity--to name only a few--the essays here make a case for constant introspection, reflection, and self questioning, so that the movement can learn and grow. They show how in India, and across much of South Asia, it is feminists who have stood against capitalism, war, violence, environmental degradation, and fundamentalism, and have forged alliances with various other movements--learning from them, working to strengthen them, and infusing them with feminist analysis. Focusing on the post-1980 period of the Indian feminist movement--a moment rich in new and different modes of resistance and of widespread political engagement with issues of rights, justice, and identity--Indian Feminisms is a comprehensive and valuable glimpse into the history of modern activism.